Chikungunya virus: A general overview - Galán Huerta, Kame Alberto; Rivas Estilla, Ana María; Fernández Salas, Ildefonso; Farfán Ale, José Arturo; Ramos Jiménez, Javier (UANL. Facultad de Medicina, 2015)
Chikungunya virus (CHIKV) is a re-emerging mosquito borne alphavirus responsible for the recent outbreak in the Americas. Immunologically naïve population in the Americas favors the spread of epidemics. Chikungunya fever is characterized by an abrupt febrile illness, polyarthralgia and maculopapular rash. In chikungunya fever, shock or severe hemorrhage is very rarely observed; the onset is more acute and the duration of fever is shorter than dengue disease. The pain is much more pronounced and localized to the joints and tendons in chikungunya fever, in comparison to dengue fever. There is no specific and effective antiviral therapy and vaccines are still in trails. The only effective preventive measures consist of individual protection against mosquito bites and vector control. Disease prevention is important due to the economic burden it entails. Clinicians need to distinguish chikungunya fever between dengue fever and other diseases to give a successful treatment and prevent disease spreading.